Influence of Cluster Type Business Agglomerations for Development of Entrepreneurial Activities. Study about Romania - Adriana Reveiu; Marian Dârdala (Amfiteatru Economic Journal, 2015)
Entrepreneurial activities relate each with the other, their features are usually, linked to the region. Many theoretical papers analyse the relationship between economic agglomerations and entrepreneurship. However, only few case studies exist, having the goal to prove the type relationship between cluster type business agglomerations and entrepreneurial activities, from the same geographical region. It seems that it is not such of analysis available for Romania, from our information. This paper aims to analyse the influence of business agglomerations, of cluster type, on the entrepreneurship. The analysis talk about to the case of Romania, and is performed throughout all the country. The originality of this paper consists in the development of analysis at the lowest level of aggregation of spatial data, namely local administrative unit (LAU) level: village, town, and city. This offers great flexibility to the analysis, because administrative grouping of LAU in: counties, regions or macro-regions, is not usually linked by the business decisions. To develop the research and to prove the nature of relationship between existing business environment and entrepreneurial activities, has been used a research methodology based on spatial statistics and Geographic Information System (GIS) analysis. The methodology proposed in the paper is applied and validate in a case study. Research results proved that there is a positive correlation between the business environment, represented by cluster type economic agglomerations, from a region and entrepreneurial activities developed, in the same region.
Keywords: L26; R12; 330; entrepreneurship; business agglomeration; spatial data analysis; economic geography